ANALISIS PERBANDINGAN PENGGUNAAN METODE BINARY SEARCH DENGAN REGULAR SEARCH EXPRESSION - Fenina Adline Twince Tobing; Rena Nainggolan (Universitas Methodist Indonesia, 2020)
The search system is a feature that is indispensable for an application or website. By comparing two algorithms that are often used, namely Binary Search and Regular Search Expression (REGEX) algorithms in a simple search system is a problem that will be discussed in this journal. Analysis of the two algorithms is carried out to solve problems in the search system so that the search algorithm can be applied more precisely and effectively. The results prove that the Binary Search has the advantage of searching large amounts of data in an ordered state and has a more effective iteration. While the Regular Expression Search has the advantage of performing searches that are not completely known about the results and keys, besides that this algorithm also allows you to search based on certain patterns in the data.